Analyzing Political Trends and Discourse on Twitter of Influential Indonesian Accounts - Hayat, Muzahid Akbar; Soraidah, Sri Mariati; Rofif, Muhammad Naufal; Asriani, Annisa Rira; Parihin, Parihin (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2024)
Social media, particularly Twitter, has become a pivotal platform for political discourse, with influential accounts shaping public opinion and political conversations. This study focuses on @yunartowijaya and @PartaiSocmed, influential Indonesian political accounts, to analyze their tweets using text analysis and data mining. The research aims to uncover prevailing political trends and subjects, shed light on the impact of these accounts on public opinion, and understand the dynamics of their interactions on social media. Through sentiment analysis and topic clustering, the study provides valuable insights into the role of social media in modern politics and how specific actors shape political conversations and influence Indonesian politics on Twitter. The findings have practical implications for refining digital-era political communication strategies, offering valuable knowledge about the digital political landscape. The research enhances our understanding of the impact of influential Twitter accounts on public opinion and political discourse, providing insights for policymakers, political practitioners, and the public.Keywords: Twitter, political discourse, social media, sentiment analysis, data mining, public opinion, digital-era politicsABSTRAKMedia sosial, khususnya Twitter, telah menjadi platform penting untuk wacana politik, dengan akun-akun berpengaruh membentuk opini publik dan percakapan politik. Penelitian ini berfokus pada akun @yunartowijaya dan @PartaiSocmed, akun politik Indonesia yang berpengaruh, untuk menganalisis tweet mereka menggunakan analisis teks dan penambangan data. Penelitian ini bertujuan untuk mengungkap tren politik yang dominan, memberikan gambaran tentang dampak akun-akun ini terhadap opini publik, dan memahami dinamika interaksi mereka di media sosial. Melalui analisis sentimen dan pengelompokan topik, penelitian ini memberikan wawasan berharga tentang peran media sosial dalam politik modern dan bagaimana aktor khusus membentuk percakapan politik serta memengaruhi politik Indonesia di Twitter. Temuan ini memiliki implikasi praktis untuk menyempurnakan strategi komunikasi politik era digital, memberikan pengetahuan berharga tentang lanskap politik digital. Penelitian ini meningkatkan pemahaman kita tentang dampak akun Twitter yang berpengaruh terhadap opini publik dan percakapan politik, memberikan wawasan bagi pembuat kebijakan, praktisi politik, dan masyarakat umum.Kata Kunci: Twitter, wacana politik, media sosial, analisis sentimen, penambangan data, opini publik, politik era digital